(untitled) - Willis, Tearon (Canada, 2006)
This book is aimed at readers who wish to learn to program using Visual Basic .NET. It assumes you have no prior experience of programming, but moves at a fast enough pace to be interesting if you have programmed in another language.
Keywords: Microsoft visual basic,Basic (computer program language)